Weighted Multi-marker Genetic Risk Scores for Incident Coronary Heart Disease among Individuals of African, Latino and East-Asian Ancestry - Carlos Iribarren (Nature Portfolio, 2018)
Abstract We examined the clinical utility of two multi-locus genetic risk scores (GRSs) previously validated in Europeans among persons of African (AFR; n = 2,089), Latino (LAT; n = 4,349) and East-Asian (EA; n = 4,804) ancestry. We used data from the GERA cohort (30–79 years old, 68 to 73% female). We utilized two GRSs with 12 and 51 SNPs, respectively, and the Framingham Risk Score (FRS) to estimate 10-year CHD risk. After a median 8.7 years of follow-up, 450 incident CHD events were documented (95 in AFR, 316 in LAT and 39 EA, respectively). In a model adjusting for principal components and risk factors, tertile 3 vs. tertile 1 of GRS_12 was associated with 1.86 (95% CI, 1.15–3.01), 1.52 (95% CI, 1.02–2.25) and 1.19 (95% CI, 0.77–1.83) increased hazard of CHD in AFR, LAT and EA, respectively. Inclusion of the GRSs in models containing the FRS did not increase the C-statistic but resulted in net overall reclassification of 10% of AFR, 7% LAT and EA and in reclassification of 13% of AFR and EA as well as 10% LAT in the intermediate FRS risk subset. Our results support the usefulness of incorporating genetic information into risk assessment for primary prevention among minority subjects in the U.S.